Human Resource Management in Improving Employee Skills - Agustina, Fitria; Nabilah Maulidah Az-Zahroh; Ahmad Dhani Syahrudin; Iriani Ismail (PT FORMOSA CENDEKIA GLOBAL, 2024)
The aim of this research is to identify human resource management in improving employee skills in minimarkets located on Jl Raya Telang No.1, Perumaan Telang Indah, Telang, Kamal, Bangkalan Regency. The method used is descriptive qualitative. This research uses information data collection methods through interviews with target sources, image documentation, location surveys. The results of our research show that human resource management in improving employee skills at the Abell Store which is applied at SRC Abell can be said to be appropriate. Starting from recruitment, to determining new employees